Electrochemistry‐Induced Improvements of Mechanical Strength, Self‐Healing, and Interfacial Adhesion of Hydrogels. Issue 40 (21st August 2021) - Miao, Yan; Xu, Mengda; Zhang, Lidong
Abstract: Hydrogels have demonstrated great potential in biomedical and engineering areas. To improve the physical performance, development of efficient physical/chemical protocols is essential. Herein, an electrochemistry functionalization strategy that is capable of enabling the functional improvements of hydrogel is reported. The electrochemistry functionalization is demonstrated on a hydrogel model of polyacrylamide (PAAm)@κ‐carrageenan. The electrochemistry reaction generates metal ions (Fe 3+ ) that migrate and coordinate with the sulfate groups of κ‐carrageenan resulting in the prominent function improvements. In comparison with untreated PAAm@κ‐carrageenan hydrogel, it can improve the mechanical strength by 7.37 times, and can increase the interfacial adhesion energy of the hydrogel on a glass surface from 0 to 1400 J m −2, stronger than the bonding strength of tendons (adhesion energy: ≈800 J m −2 ). Two pieces of hydrogel strips integrate into an intact structure by the electrochemistry functionalization, where the healing efficiency reaches 100% in comparison to the untreated hydrogel. The most significant development is that it enables functional patterning on the hydrogel by the electrode assembly, which provides the hydrogel with modular sensitivity to external pressure. Therefore, it can be a general protocol for rapid generation of multifunctional hydrogels for biomedical and engineering developments. Abstract : An electrochemistry strategy to enable functional improvements of hydrogels is reported. In comparison with an untreated one, the mechanical strength can be improved by 7.37 times, the interfacial adhesion energy to 1400 J m −2, and the healing efficiency to 100%, showing a general feature for the rapid generation of multifunctional hydrogels for biomedical and engineering applications.